If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 2n + -4 = n + -10 Reorder the terms: -4 + 2n = n + -10 Reorder the terms: -4 + 2n = -10 + n Solving -4 + 2n = -10 + n Solving for variable 'n'. Move all terms containing n to the left, all other terms to the right. Add '-1n' to each side of the equation. -4 + 2n + -1n = -10 + n + -1n Combine like terms: 2n + -1n = 1n -4 + 1n = -10 + n + -1n Combine like terms: n + -1n = 0 -4 + 1n = -10 + 0 -4 + 1n = -10 Add '4' to each side of the equation. -4 + 4 + 1n = -10 + 4 Combine like terms: -4 + 4 = 0 0 + 1n = -10 + 4 1n = -10 + 4 Combine like terms: -10 + 4 = -6 1n = -6 Divide each side by '1'. n = -6 Simplifying n = -6
| 2x+2=3x-63 | | 4(-2+5)=-2(4x+5) | | 2-8(2+7n)=6n+34 | | 2x+20=6x+24 | | -(5y+6)= | | x-27.9=4x | | 5x-7x-15=-2x+8-15 | | 3x-17=98 | | .60(p)=p-32 | | -(3y+4)= | | 7z-2z=30 | | 0.12(y-9)+0.04y=0.14y-0.09(10) | | -5c(c-8c)= | | 2.8x=5.1 | | y/(-4)+5=15 | | 6t-2(5+4t)=5+2t | | .5x+.33(3x)=3 | | (2a+3b)(2a+3b)= | | x=7x-45 | | 72x^3-50x=0 | | 5/24+1/8=25/40 | | (2a+3b)2= | | S=4p+4q | | 4(m+9)=2(m-5)+2 | | 6x+5=-x+40 | | w-10=-1 | | 3x+5=(x-9) | | n+9=-14 | | -2h=22 | | 0.60+p=32 | | |x+4|=1 | | 2v^2=16 |